DETERMINAN HARGA EMAS DI INDONESIA: PENDEKATAN ARDL PADA PERIODE SETELAH PANDEMI COVID-19 - Nandya Artha Dyanti; Tiara Nirmala (Bhinneka Multidisiplin Journal, 2026)
This study examines the determinants of gold prices in Indonesia during the post-COVID-19 period from January 2023 to April 2026 using the Autoregressive Distributed Lag (ARDL) approach. The analysis focuses on the Indonesian Composite Stock Price Index (IHSG), inflation, the USD to Rupiah exchange rate, and oil prices (USOIL). The results indicate a long-run relationship between gold prices and the selected macroeconomic variables. The IHSG, inflation, and the exchange rate have positive and significant effects on gold prices, while oil prices are found to be insignificant. These findings suggest that domestic financial market conditions, inflationary pressures, and exchange rate fluctuations play an important role in determining gold prices in Indonesia. Overall, the results support the role of gold as both a hedging instrument and a safe-haven asset amid economic uncertainty in the post-COVID period.